The Effects of Digital Transformation on Firm Performance: Evidence from China’s Manufacturing Sector - Lei Guo (MDPI AG, 2021)
With vast potentials in improving operations and stimulating growth, digital transformation has aroused much attention from firms across the world. However, the high costs associated with the transformation can not be ignored. Limited research has looked into the organizational performance effects of digital transformation. After examining the benefits and costs of digital transformation, this research makes an empirical study on the impact of digital transformation on firm operational and financial performance. The panel data from 2010 to 2020 of 2254 manufacturing companies in China suggests that the intensity of digital transformation is in positive correlation with the process-based operating performance, and in the U-shaped correlation with the profit-oriented financial performance. Further, we find that digital transformation has a much more lasting impact on operating performance than on financial performance. The conditions required (i.e., policy and innovation environment) to improve the operating performance via digital transformation are more easing. This research shows the differentiated effect of digital transformation on different dimensions of organizational performance and provides guidance for companies to set the goals for digital transformation.